engaruh price value terhadap minat beli konsumen pada aplikasi pesan antar makanan dengan variabel sikap sebagai mediasi - Rakhmawati, Novita; Farisi, Herdian (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
The study aims to test the influence of price value on consumer purchase intentions on the Food Delivery Application (FDA), using the variable of attitude as a mediator. questionnaires as the main tool in quantitative research approaches. Purposive sampling was used to choose samples of up to 100 responders. The findings of the structural equation modeling (SEM) analysis demonstrate that pricing value and attitude have a positive and substantial relationship. However, price value does not directly influence consumer purchase intentions, whereas the relationship between price value and purchasing intention is mediated by attitude. Implicitly, service providers should focus on pricing strategies that provide good value for consumers to harness this influence and drive business growth.